Kontribusi Ekonomi Islam Dalam Pembangunan Ekonomi - Agustina Nurul Hidayah; Innamatul Khoiroh; Muhammad Zamzam Badi’uzzaman; Sofiana Putri Nur Aini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research examines the contribution of Islamic economics to economic development through instruments such as Baitul Mal Wattamwil (BMT), sukuk, sharia banks and waqf banks. The method used is a literature study with secondary data analyzed using content analysis. The research results show that Islamic economics makes an important contribution to economic development in Indonesia. BMT increases employment opportunities and reduces poverty, sukuk plays a role in state financing and infrastructure, sharia banks contribute to financing the real sector and social services, while waqf banks empower the community's economy. Islamic economics is an alternative economic development that pays attention to moral and social aspects, not just growth.